2013
DOI: 10.1186/1476-4598-12-99
|View full text |Cite
|
Sign up to set email alerts
|

Mahanine restores RASSF1A expression by down-regulating DNMT1 and DNMT3B in prostate cancer cells

Abstract: BackgroundHypermethylation of the promoter of the tumor suppressor gene RASSF1A silences its expression and has been found to be associated with advanced grade prostatic tumors. The DNA methyltransferase (DNMT) family of enzymes are known to be involved in the epigenetic silencing of gene expression, including RASSF1A, and are often overexpressed in prostate cancer. The present study demonstrates how mahanine, a plant-derived carbazole alkaloid, restores RASSF1A expression by down-regulating specific members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 35 publications
6
83
0
1
Order By: Relevance
“…In addition to Western drugs, phytochemicals have also been found to possess chemoprevention effects via epigenetic alterations (15). For example, mahanine, a carbazole alkaloid found abundantly in some Asian vegetables, has been reported to be a DNA hypomethylation agent that restored the expression of an epigenetically silenced tumor suppressor gene due to the inhibitory effect of DNMTs (16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Western drugs, phytochemicals have also been found to possess chemoprevention effects via epigenetic alterations (15). For example, mahanine, a carbazole alkaloid found abundantly in some Asian vegetables, has been reported to be a DNA hypomethylation agent that restored the expression of an epigenetically silenced tumor suppressor gene due to the inhibitory effect of DNMTs (16).…”
Section: Introductionmentioning
confidence: 99%
“…Mahanine did not induce degradation of DNMT3B and DNMT1 in constitutively active Akt-expressing cells, suggesting that mahanine exerted inhibitory effects on wild-type Akt. 9 Similarly, hepatitis B virus X protein (HBx; HBVgp3) negatively regulates RASSF1A. For example, HBx-positive cells markedly reduce RASSF1A expression and are associated with markedly higher expression of DNMT3B and DNMT1.…”
Section: Dnmt-mediated Inactivation Of Rassf1amentioning
confidence: 99%
“…12,13 Regulation of RASSF1A is thought to be mediated by DNMT proteins in responses to natural products and to viral infection. 9 For example, mahanine, a plant-derived carbazole alkaloid, was reported to restore expression of RASSF1A in prostate cancer cells. Mechanistically, it was shown that mahanine induced DNMT3B and DNMT1 degradation and reduced nuclear accumulation of both these enzymes.…”
Section: Dnmt-mediated Inactivation Of Rassf1amentioning
confidence: 99%
“…The actives were positive controls or compounds that showed inhibitory activity against DNMT1 through in vitro or in vivo tests. Based on the previous research, 25 compounds were chosen as actives [11][12][13][14][15][16][17]. Their structures were obtained in SMILES format from the PubChem website at pubchem.ncbi.nlm.nih.gov [33].…”
Section: Preparing the Ligand Structurementioning
confidence: 99%
“…Natural products are promising non-nucleoside DNMTi candidates because of their relatively low toxicity and high structural diversity [10,11]. The potential of several natural products has been studied; these products have included curcumin [12], epigallocatechin (EGCG) [13], genistein [14], caffeic acid [15], psammaplin A [16], mahanine [17], and laccaic acid [16]. However, the inhibitory effects of these natural compounds are relatively low [11].…”
Section: Introductionmentioning
confidence: 99%